The Influence Of Brand Image On Purchase Decisions Through Purchase Interest : (Consumer Study of Mugwort Clay Stick Mask Skintific) - Cahyani, Winda; Wisnu Usdek Riyanto, Dicky; Rahman Hakim, Arif (Universitas muhammadiyah malang, 2024)
This study aims to describe the condition of brand image, purchase intention and purchase decision, analyze the influence of brand image on purchase decision, analyze the influence of brand image on purchase intention, analyze the influence of purchase intention on purchase decision, analyze the role of purchase intention in mediating the influence of brand image on purchase decision. The population in this study were consumers of mugwort clay skintific in Malang City with a total of 110 respondents using purposive sampling technique. The method used was the process macro hayes with SPSS 25. The results of this study indicate that brand image has a significant positive effect on purchase decision, brand image has a significant positive effect on purchase intention, purchase intention has a significant positive effect on purchase decision and purchase intention can mediate the influence of brand image on purchase decision.